Accounting disclosure for social responsibility in the annual financial statements and reports_A field study of a sample of Algerian industrial enterprises - dachir, malika; Ikhlef , Abderrezak (Journal of Research in Finance and Accounting, 2021)
This study aimed to shed light on the extent of the commitment of Algerian industrial enterprises to disclose their social responsibility in their lists and financial reports, and to stand at the most important difficulties that limit these institutions' disclosure of their social responsibility, by distributing 56 questionnaires to decision-makers in ten industrial institutions. The study concluded that the Algerian industrial enterprises inadequately disclose their social responsibility in the financial statements and reports they issue, and this is due to a set of difficulties, the most important of which are: the lack of legal legislation binding on the disclosure of social responsibility activities, and the lack of a clear model for disclosing this responsibility.